The Coral Reef Health Disturbance in The Waters of Pongok Island, South Bangka District - Firmansyah, Muhammad; Adibrata, Sudirman; Muftiadi, M. Rizza; Perangin-angin, Robet (Coastal and Marine Journal, 2024)
This research aims to analyze coral reef cover and analyze coral reef health problems. This research was conducted in October 2023 in the waters of Pongok Island. Coral reef cover data collection using the method of Underwater Photo Transect (UPT) and data collection on the distribution of coral health disorders was taken using the belt transect method (belt transect). The results of the research showed that the percentage of coral reef cover in Pongok Island waters ranged from 28.67% - 63.87% which was categorized as Medium to Good. Coral reef health problems found at the research location in Pongok Island waters are Bleaching (B), Sedimentation damage (SD), Pigmentation response (PR), growth anomalies (GA), and crown of thorns starfish (CoTS). Sedimentation damage is the highest prevalence in the research location with 3.42%, then pigmentation response (PR) with a total of 0.48%, Crown of thorns starfish (CoTS) 0,05%, Bleaching (B) 0,04%, and Growth anomalies (GA) with an amount of 0.01%.